Perancangan dan Implementasi Manajemen Digital Marketing pada Sosial Media Instagram Elegancia Patisserie - Karen Fu; Immanuel Zai (Cv. Utility Project Solution, 2022)
Advances in information technology have influenced how marketing is carried out in different industrial sectors, especially with the existence of various platforms and methods to increase consumer brand awareness. Digital marketing strategies such as social media marketing, video & photo marketing, content marketing and discounts. This article implements this strategy for MSME (Micro, Small and Medium Enterprises) Instagram social media in Indonesia, namely: Elegancia, because MSMEs are one of the supporters of economic growth. Based on this, the design of this article was carried out using secondary data which is data obtained from other parties and officially published which can be obtained by means of literature studies as well as documentation data and available report data. Apart from that, this research is also a qualitative research, in which data collection comes from observations, interviews and research. Thus the results of this implementation prove the benefits of using digital marketing such as: content marketing, social media and discounts in increasing brand awareness resulting in a consistent increase in MSME Instagram social media.